ELASTICS ANALYSIS OF SLAB MULTILAYERED PROGRAMMING (EAOSM) - Abdi, Fachriza Noor (APLIKA Jurnal Ilmu Pengetahuan dan Teknologi, 2008)
Development of layered finite elements model of reinforced concrete slab structures which is implemented in a program EAoSM (Elastics Analysis of Slab Multilayered) is outlined. The program is based on a layering formulation in which the cross section is divided into steel and concrete layers. Concrete layers are simulated with 8-nodes isoparametric quadratic quadrilateral plane stress and Mindlin plate elements; steel layers are modeled with plane stress elements. Interlayer compatibility is satisfied by constraining in-plane displacements along common interfaces to be the same for adjacent layers which the central layer is assumend to be the reference layer. An efficient algorithm is used for assembly of the stiffness matrix, constraints matrix and solution of the equations.